Firms and the Decline in Earnings Inequality in Brazil - Alvarez, Jorge (IMF Working Papers; Working Paper ;, 2017)
We document a large decrease in earnings inequality in Brazil between 1996 and 2012. Using administrative linked employer-employee data, we fit high-dimensional worker and firm fixed effects models to understand the sources of this decrease. Firm effects account for 40 percent of the total decrease and worker effects for 29 percent. Changes in observable worker and firm characteristics contributed little to these trends. Instead, the decrease is primarily due to a compression of returns to these characteristics, particularly a declining firm productivity pay premium. Our results shed light on potential drivers of earnings inequality dynamics.